Treat the patient not the blood test: the implications of an increase in cardiac troponin after prolonged endurance exercise. Issue 9 (29th January 2007) - Whyte, G; Stephens, N; Senior, R; George, K; Shave, R; Wilson, M; Sharma, S
Abstract : Collapse after prolonged endurance exercise is common and usually benign. This case study reports a triathlete who suffered a vaso-vagal associated collapsed after exercise. Misdiagnosis of myocardial injury in the presence of elevated cardiac troponins and ECG anomalies led to inappropriate management and highlights the difficulty in treating the collapsed athlete following arduous exercise.